Efforts to Prevent Breast Cancer Through BSE - Priharyanti Wulandari; Dwi Nur Aini; Mariyati Mariyati; Arifianto Arifianto (Global Health Science Group, 2020)
Breast cancer is one of the most common types of cancer in Indonesia. Based on Pathological Based Registration in Indonesia, breast cancer ranks first with a relative frequency of 18.6%. More than 80% of cases are found to be at an advanced stage, in addition as many as 60-70% of breast cancer treatment seekers are already in an advanced stage so treatment is difficult. Therefore it is necessary to understand prevention efforts and early diagnosis so that patient detection can be carried out at an early stage so that it can reduce breast cancer deaths. Breast cancer screening is an examination or attempt to find abnormalities that lead to breast cancer in a person or group of people who have no complaints. The initial attempt to screen for breast cancer is BSE. The purpose of this community service activity is to hold BSE training at SMA Setia Budi Semarang to improve student skills in independent breast examination. The BSE training activities for SMA Setia Budi Semarang students were carried out by providing counseling using the lecture and demonstration method which was held on October 15, 2019. The attendance of participants at the counseling was 47 people. The results of the activities of SMA Setia Budi Semarang students not only require information about breast cancer but also require information on women's reproductive health as a whole.